Social Work or Relief Work? A Crisis in Professional Social Work - Adhikari Harasankar (Social Change Review, 2015)
Social work is a sharing and caring profession based on scientific methods. This problem solving profession makes people self-reliant and self-dependent when he/she is in any sorts of crises. Thus, it differs from relief work, social services or social welfare delivered during emergence crises. This paper examined the application of professional social work as relief work, which did not bring any change among the beneficiaries; rather it set their mind as opportunist. For this purpose, the programme sponsored by the government of India and implemented by nongovernmental organizations for rehabilitation of the street children (i.e., pavements and slums dwellers, children of sex workers, and so forth) of Metro cities like Kolkata had priority. This evaluative study assessed the progress and changes among 500 street children who were the beneficiaries for 10 years of the programme, selected according to their parental residents/occupation through stratified sampling. Interviews, case studies and group interaction were used to collect data on various aspects, i.e. personal background, education, and occupation of these children. It revealed that after almost 10 years of services, the problem of children was static. Firstly, service delivery system was as relief work. The methods of social work were not implied while the professionals were in implementation. On the other hand, the scope of monitoring and evaluation of the programme by government was suspended due to several reasons. Definitely, the politicalization in human development would be restricted. The problems of suffering would be root out and it should not be a continued process.